Just in case, just in time, or just don't bother? Assessment of one-shot library instruction with follow-up workshops - Daland, Hilde Terese (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2015)
This article examines if the timing of library instruction courses is an important part of how students experience library instruction as a means of developing information literacy skills.  Two student groups, belonging to different academic subjects, have received the same training and the same assessment questionnaire afterwards. One of the groups was in the middle of writing their student thesis as a part of their final year of their bachelor degree work, the other group consisted of different subjects within the humanities and they were not working specifically with an assignment. Research shows that student’s information seeking skills have not significantly changed over the last some 25 years. One may argue that information literacy skills are so practical that they cannot be taught in a classroom with a theoretical approach. One may also wonder how timing of library instruction affects the learning outcome for students.